2020
DOI: 10.3390/cancers12113167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Low Prognostic Nutritional Index and High Intramuscular Adipose Tissue Content on Outcomes of Patients with Oral Squamous Cell Carcinoma

Abstract: The impact of preoperative malnutrition and sarcopenia on survival in oral squamous cell carcinoma (OSCC) patients remains controversial. We investigated the effects of the preoperative nutritional status and abnormalities in body composition on the mortality of OSCC patients. A retrospective study involving 103 patients with OSCC was conducted. Disease-specific survival (DSS) according to the preoperative psoas muscle mass index (PMI) and intramuscular adipose tissue content (IMAC) was evaluated. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…There are several ways to measure muscle quantity. Namely, cross-sectional area of a specific muscle group or body part, total body skeletal muscle mass, or appendicular skeletal muscle mass, although there is still debate as to which method is superior [ 13 ]. On the other hand, it has been reported that measurement of the psoas muscle at the L3 level using CT for assessing muscle quantity is useful in predicting morbidity in a variety of conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several ways to measure muscle quantity. Namely, cross-sectional area of a specific muscle group or body part, total body skeletal muscle mass, or appendicular skeletal muscle mass, although there is still debate as to which method is superior [ 13 ]. On the other hand, it has been reported that measurement of the psoas muscle at the L3 level using CT for assessing muscle quantity is useful in predicting morbidity in a variety of conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since the psoas area estimates both muscle and intramuscular adipose tissue, PMI does not always indicate actual muscle mass because the areas of psoas muscles evaluate both muscle and intramuscular adipose tissue [ 23 ]. In our previous study, OSCC patients with preoperative low muscle quantity as defined by low PMI and low muscle quality as defined by high IMAC had significantly lower disease-specific survival than controls [ 13 ]. These results suggest that there is a substantial interaction between the preoperative comorbidity of sarcopenia and the mortality of patients with OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also has therapeutic implications. Regular dietary counseling and nutritional intervention might help patients with HNC who are at nutritional risk or have low M-SMI to minimize muscle atrophy, maintain their body weight, and prevent severe malnutrition, thereby improving their survival outcomes and quality of life [31][32][33].…”
Section: Plos Onementioning
confidence: 99%